Intake of dietary flavonoids in relation to overactive bladder among U.S. adults: a nutritional strategy for improving urinary health - Lin, Chaohuan; Lyu, Jie; Feng, Zhen (Frontiers in Nutrition, 2024)
Background: The increasing influence of overactive bladder (OAB) on physical as well as mental health of individuals is becoming more pronounced annually, as evidenced by the urge urinary incontinence and nocturia. Symptoms in OAB patients may be influenced by inflammation and oxidative stress. Flavonoids are recognized as significant anti-inflammatory and antioxidant agents, which are commonly available in fruits, tea, vegetables, etc. Despite this, there remains a paucity of research exploring the potential correlation between flavonoid consumption, specifically within distinct subclasses, and OAB. Methods: We utilized the survey data from the National Health and Nutrition Examination Survey (NHANES) and the USDA Food and Nutrient Database for Dietary Studies (FNDDS) to investigate the relationship between dietary intake of total and subclass flavonoids and the risk of OAB based on 13,063 qualified American adults. The dietary flavonoid intake was estimated from two 24-hour dietary recalls. Weighted multivariate logistic regression model, quantile-based g-computation, restricted cubic spline model, and stratified analysis were used to explore the association between flavonoid intake and OAB, respectively. Results: The participants diagnosed with OAB exhibited a higher percentage of being female, older, Non-Hispanic Black, unmarried, former drinkers, having a lower annual household income, lower poverty to income ratio, lower educational attainment, and a higher likelihood of being obese and smokers. Upon adjusting for confounding factors, the weighted logistic regression models revealed that the third quartile of consumption of anthocyanidin and the second quartile of consumption of flavone were significantly associated with the reduced odds of OAB, while total flavonoid consumption did not show a significant correlation with the risk of OAB. The quantile-based g-computation model indicated that flavone, anthocyanidin and flavonol were the primary contributors to the observed negative correlation. Furthermore, the restricted cubic spline models demonstrated a J-shaped non-linear exposure-response association between anthocyanidin intake and the risk of OAB (Pnonlinear = 0.00164). Conclusion: Our research suggests that consuming a diet rich in flavonoid subclass anthocyanidin and flavone is associated with a reduced risk of OAB, potentially offering clinical significance in the prevention of OAB development. This underscores the importance of dietary adjustments in the management of OAB symptoms.